1990
DOI: 10.1063/1.1141975
|View full text |Cite
|
Sign up to set email alerts
|

Visible charge exchange spectroscopy at JET

Abstract: Calibration of the charge exchange recombination spectroscopy diagnostic for core poloidal rotation velocity measurements on JET Rev. Sci. Instrum. 75, 3452 (2004); 10.1063/1.1784531Real-time analysis of charge-exchange spectroscopy data at JET Recent developments and results of the JET CXRS diagnostic are reported. The measurements of radial profiles of ion temperatures and densities are based on CXR spectra of fully stripped ions of either carbon or beryllium. Considerable effort has been expended in ensurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 9 publications
0
49
0
Order By: Relevance
“…Apart from the standard data routinely available in JET, the main diagnostics used for the studies reported here were the ECE heterodyne radiometer (KK3) [8] and CXRS (KS5) [9] for electron and ion temperature measurements, respectively, and the horizontal (KR2) and vertical (KF1) neutral particle analysers (NPAs) [10,11] for the assessment of fast ion tails eventually created due to ICRF acceleration. The latter were complemented by measurements of fast ion losses performed with the scintillator probe KA3 [12].…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Apart from the standard data routinely available in JET, the main diagnostics used for the studies reported here were the ECE heterodyne radiometer (KK3) [8] and CXRS (KS5) [9] for electron and ion temperature measurements, respectively, and the horizontal (KR2) and vertical (KF1) neutral particle analysers (NPAs) [10,11] for the assessment of fast ion tails eventually created due to ICRF acceleration. The latter were complemented by measurements of fast ion losses performed with the scintillator probe KA3 [12].…”
Section: Experimental Set-upmentioning
confidence: 99%
“…JET is equipped with diagnostics that allow pinning down the temperature profiles with sufficient spatial and temporal resolution to yield meaningful results about where the externally launched waves transfer their energy to the plasma. The ion temperature profile is obtained via charge exchange diagnostics [31], while the electron temperature profile is estimated from electron cyclotron emission measurements [32].…”
Section: Development Of Icrf Heating Schemes For Iter's Non-active Phasementioning
confidence: 99%
“…C q+ ) in the plasma and injected fast neutral atoms, like e.g. H, He, or Li, to measure ion densities (von Hellermann et al 1990, Schorn et al 1991, Mandl et al 1993, temperatures (von Hellermann et al 1990, Schorn et al 1992, Mandl et al 1993, velocities of plasma rotation, and Z eff , the effective charge of the plasma (Isler 1994, Wolfrum et al 1993, Boileau et al 1989.…”
Section: Introductionmentioning
confidence: 99%